Three-dimensional equalization of ultrawideband antenna distortion - Malik, W; Edwards, D; Zhang, Y; Brown, A (2007)
A typical ultrawideband (UWB) antenna acts as a space-frequency filter. As a result, the UWB signal transmitted or received by such an antenna undergoes joint angular-spectral distortion, and consequently the system suffers serious performance degradation. We discuss a technique to compensate for this distortion and recover the original signal using multiple antenna arrays. To evaluate its performance, the proposed technique is applied to UWB signal propagation in an indoor multipath environment simulated using a specialized ray-tracing approach. The results demonstrate that our antenna equalization scheme significantly reduces the effect of small-scale fading introduced by the antennas, and can therefore improve the performance of a UWB communications link as well as facilitate the extraction of antenna-independent channel measurements. © 2007 IEEE.